Suction in percutaneous nephrolithotripsy: evolution, development, and outcomes from experimental and clinical studies. Results from a systematic review - TANIDIR, YILÖREN (My University, 2023)
Context: Controversy exists regarding the therapeutic benefit of suction use during percutaneous nephrolithotripsy (PCNL). Objective: To review and highlight the options available in the use of suction for PCNL, and to discuss their strengths and limitations. Evidence acquisition: A systematic literature search was performed using Scopus, EMBASE, and PubMed. Thirty four studies were included. There was one ex vivo study. Among clinical studies, 24 used a vacuum/suctioning sheath and nine a handpiece suction device/direct-in-scope suction. The suction technique was employed in standard, mini-PCNL, supermini-PCNL, and enhanced supermini‑PCNL techniques. Evidence synthesis: Handpiece suction devices demonstrated better safety and efficiency in treating large stones than nonsuction PCNL and in a much shorter time. Trilogy and ShockPulse-SE were equally effective, safe, and versatile for standard PCNL and mini-PCNL. The heavier handpiece makes Trilogy less ergonomically friendly. Laser suction handpiece devices can potentiate laser lithotripsy by allowing for better laser control with simultaneous suction of small fragments and dust. Integrated suction-based sheaths are available in reusable and disposable forms for mini-PCNL only. Mini-PCNL with suction reported superior outcomes for operative time and stone-free rate to mini-PCNL. This also helped minimize infectious complications by a combination of intrarenal pressure reduction and faster aspiration of irrigation fluid reducing the risk of sepsis, enhance intraoperative vision, and improve lithotripsy efficiency, which makes it a very attractive evolution for PCNL. Conclusions: Suction devices in PCNL are reforming the way PCNL is being done. Adding suction to mini-PCNL reduces infectious complications and improves the stone-free rate. Our review shows that despite the limited evidence, suction techniques appear to improve PCNL outcomes. Patient summary: In this review, we looked at the intra- and perioperative outcomes of percutaneous nephrolithotripsy (PCNL) with the addition of suction. With better stone fragmentation and fewer postoperative infections, this technology is very useful particularly for mini-PCNL.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; Kidney calculi; Lithotripsy, Laser; Percutaneous nephrolithotomy; Sheath; Suction